Chromosomal evolution in allopatric populations of the Odontophrynus occidentalis group (Amphibia, Anura) from western Argentina - Ruiz, Itamar Romano García (1982)
A karyological study of some populations of the Odontophrynus occidentalis group (2n=22) from Argentina is reported. Ammoniacal silver (Ag-AS) and alkaline Giemsa (CBG) staining have been performed on specimens from La Rioja, Mendoza, Malargue, Tamelen, Tapiluque, Valcheta, and Meseta de Somuncura. All populations showed active ribosomal cistrons (NORs) on chromosome 11. Some metaphases of three specimens from Mendoza and five from La Rioja also showed bands on 9. Centromeric and telomeric C-bands were common to all populations, and a block of heterochromatin on both sides of the centromere of 2 was remarkable in all but the La Rioja populations. The specimens from La Rioja showed a similar block of heterochromatin on the short arm of 1. Taxonomic studies of several specimens from these localities revealed differences in larval development, glandular pattern, the size of specimens, etc. As a whole, biological as well as karyological features suggest that the isolated population at La Rioja is a separate entity, at the species level, as described elsewhere.